Public accountability and administrative efficiency through right to information: Opportunities and challenges - Misra, Suresh (2009)
Democracy is the only form of government, where citizens are fundamental to its survival. The public which elects the government has right to be informed of the decisions and actions of the government. Hence transparency and openness are essential for the optimum working of the democracy. A citizen's duty is not only to elect representatives, but he is also a crucial link in the day-to-day working of the government and its institutions. An important factor in the absence of popular participation in the governance process is the lack of information. The government should ensure that the electorate engages in the informed participation. This can be ensured through legislation and proactive efforts of the government. - Reproduced.
Keywords: Accountability; Right to information